Pendekatan Edukatif Berbasis Spiritual dalam Penanganan Bullying Relasional di MI Darun Najah Gading - Widyani, Reffin Laily Nur; Godly Prayitno, Abdul Afwu (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to identify and deeply understand cases of relational bullying in Indonesia, specifically at Madrasah Ibtidaiyah (MI) Darun Najah Gading using spiritually-based educational approaches as an intervention to reduce bullying behavior among students.Method – This research employs a qualitative descriptive method. The approach used to understand relational bullying is spiritual-based education. The research was conducted at MI Darun Najah Gading. Data were collected through observation, interviews, and documentation techniques at MI Darun Najah Gading. The data analysis methods employed in this study are based on the Miles and Huberman model, which includes steps such as data collection, data reduction, data display, and conclusion formulation, with the findings presented in a descriptive narrative format.Findings – The research findings indicate that a spirituality-based educational approach can serve as an effective strategy to address relational bullying. This approach is implemented through religious activities aimed at fostering students' closeness to God and strengthening their relationships with peers. The program is considered effective in shaping students' character to become more tolerant, empathetic, and respectful of one another, thereby reducing instances of relational bullying. Research Implications – This research provides significant contributions to the development of anti-bullying programs in schools, particularly those with a religious foundation. The practical implications suggest that a spiritually based educational approach can serve as an effective solution in addressing bullying issues, especially within Islamic educational settings. The implementation of similar programs in other schools could be considered as a sustainable effort to prevent relational bullying.